IOR 1997 - 9th European Symposium on Improved Oil Recovery 1997
DOI: 10.3997/2214-4609.201406794
|View full text |Cite
|
Sign up to set email alerts
|

Foam Propagation in Snorre Reservoir Core - Effects of Oil Saturation and Ageing

Abstract: A s eries of foam floods was conduct ed in Snorre re s e rvoir core at 90°C and 300 bar, at different o il saturations . The rate of foam propagation and the time requir ed to reach the maximum attainable apparent foam viscosi ty depended strongly on oil saturation. Apparent foam viscosity decreased steeply at a "critical " oil saturation of 13 to 15%. Extremely high apparent foam viscosities , up to 1000 cP, veere generated at miscible gas flood residual oil saturat i on (13%) . Above the critical oil saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…It is reasonable to believe that foam generates and propagates, according to the established tracer profile in dispersion measurement, which represents areas of lower flow resistance, as this coincided with the start of the foam plateau level in most experiments. Compared to experiments in homogeneous sandstone cores, it is often observed that the foam propagation follows the injection rate. , Thus, it seems like foam propagation in oil-free carbonates is faster than in sandstones, which could be reflecting the heterogeneous nature or the complexity of the pore structure of carbonates.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is reasonable to believe that foam generates and propagates, according to the established tracer profile in dispersion measurement, which represents areas of lower flow resistance, as this coincided with the start of the foam plateau level in most experiments. Compared to experiments in homogeneous sandstone cores, it is often observed that the foam propagation follows the injection rate. , Thus, it seems like foam propagation in oil-free carbonates is faster than in sandstones, which could be reflecting the heterogeneous nature or the complexity of the pore structure of carbonates.…”
Section: Discussionmentioning
confidence: 89%
“…Compared to experiments in homogeneous sandstone cores, it is often observed that the foam propagation follows the injection rate. 26,27 Thus, it seems like foam propagation in oil-free carbonates is faster than in sandstones, which could be reflecting the heterogeneous nature 33 or the complexity of the pore structure of carbonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wettability may, in addition to the residual oil saturation, reduce foam propagation rate as foam nucleation sites may be unavailable for foam generation. Mannhardt and Svorstøl (1997) studied foam generation and foam propagation at Snorre reservoir conditions and reported a strong dependence of foam propagation on oil saturation. Higher oil saturation reduced foam propagation and foam propagation in the absence of oil followed the injection rate.…”
Section: Co 2 -Foamsmentioning
confidence: 99%